Hard X-ray properties of radio-selected blazars - Langejahn, M.; Kadler, M.; Wilms, Jörn; Litzinger, E.; Kreter, M.; Gehrels, N.; Baumgartner, W. H.; Markwardt, C. B.; Tueller, J. (Astronomy & Astrophysics, 2020)
Context. Hard X-ray properties of beamed active galactic nuclei have been published in the 105-month Swift/BAT catalog, but there have not been any studies carried out so far on a well-defined, radio-selected sample of low-peaked blazars in the hard X-ray band.
CRIS-Team WoS Importer:2020-06-16